Valorization of seaweed carbohydrates: autohydrolysis as a selective and sustainable pretreatment - Dias, Joana Sofia Gomes (2020)
Seaweeds are promising feedstocks; nevertheless, the lack of systematic approaches to recover different high-value fractions in a clean and sustainable mode hampers their exploitation. Due to this necessity, an innovative environmentally friendly strategy was proposed in this article for the development of a sugar platform from Gelidium sesquipedale: for the first time, autohydrolysis followed by enzymatic saccharification (with cellulolytic and agarolytic cocktails) was applied to agarophyte seaweeds. The wide range of severities (between 2.47 and 4.94) studied in this work proved that the autohydrolysis-based process can be tuned to selectively extract different target carbohydrate fractions. Gelling agents (reaching 30 g/100 g DW) can be obtained by the application of low severity treatments, fermentable sugars or oligosaccharides with the nutraceutical potential (reaching 14 g/100 g DW) are produced when severity is increased, and at the highest severity, platform chemicals (reaching 4 g/100 g DW) are the final product. The reduction of processing times compared to traditional extraction methodologies and the elimination of chemicals used in dilute acid treatments make this strategy a clean and sustainable alternative for the valorization of both glucan and galactan fractions of G. sesquipedale.